Laterality in artistic gymnastics - Bessi, F. (Revista Brasileira de Educação Física e Esporte, 2016)
Worldwide trainers ask if there is a rotation scheme, which facilitate the learning of the elements with longitudinal rotations. Although there are some research on it, they did not attempt to verify a total scheme, but merely to see the relationship between two elements or four elements. In this study we analyse the appreciation of experts N = 161 coaches (age: 34.9 ± 10.9) from different levels of expertise and from different countries (ARG, BOL, BRA, CHI, ECU, ELS, GER, GUA, HON, MEX, PAN, PER, URU, VEN) with 12 ± 8.8 years of experience regardinghow gymnasts should execute 27 different elements in 5 male apparatus. We chose these elements, because we wanted to have movements with rotation in upright stance, upside down and in combination with transversal rotation. Through a questionnaire for coaches, we tried to verify if there are differences, coincidences or even immovable rules in the rotation scheme that gymnasts use (or should use). The answers were typologized with three categories of rotational preference: unilateral consistent twister, bilateral consistent twister and inconsistent twister. The study aimed to answer several questions: Do coaches agree on how the rotation scheme should be in gymnastics? How do coaches (former gymnasts) determined which way to turn? Do the handedness or the footedness infl uence on the direction of rotation? Does the personal rotation scheme infl uence on the concept of appropriate rotation scheme? Do the national practices infl uence the rotation scheme? Are there differences in appreciation between coaches at different levels? Are unambiguous rules among the elements?